Marinade with alkaline solutions for the improvement of pork quality - Santos, Viviane Maria Oliveira dos; Caldara, Fabiana Ribeiro; Seno, Leonardo de Oliveira; Feijó, Gelson Luis Dias; Almeida Paz, Ibiara Correia de LIma; Garcia, Rodrigo Garófallo; Nääs, Irenilza de Alencar; Altemio, Ângela Dulce Cavenaghi (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effects of alkaline solution marinades on the characteristics of pork subjected to post‑mortem pH decrease in pig muscle. The pH of carcasses was measured in a commercial slaughterhouse (n = 526), 45 min after slaughtering (pH45) and, then, the carcasses were divided into the groups with pH45≤5.7 or pH45>5.7. Ten samples of the longissimus dorsi muscles of each group were collected and distributed in an entirely randomized design, in a 2x4 factorial arrangement, with two conditions (pH45≤5.7 or pH45>5.7), and four marinade solutions: TC, no marinade; TM1, sodium bicarbonate and sodium chloride; TM2, sodium tripolyphosphate and sodium chloride; TM3, sodium bicarbonate, sodium tripolyphosphate and sodium chloride. There was no interaction between pH45 of the meat and the marinade treatments. Meat with pH45≤5.7 showed higher values for lightness, and for purge loss (PL), exudate loss (EL), cooking loss (CL) and shear force (SF). Marinating increased the pH, reduced the lightness, EL, CL and SF, and improved tenderness, juiciness and flavor of meat. Marinades with solutions containing chloride, bicarbonate, and sodium tripolyphosphate are effective in the improvement of pork quality, making physical characteristics of marinated meat similar to those of fresh pork, as a consequence of accelerated postmortem glycolysis.